2016
DOI: 10.1002/minf.201600126
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hERG Liability – Using SVM Classification, Bootstrapping and Jackknifing

Abstract: Drug-induced QT prolongation leads to life-threatening cardiotoxicity, mostly through blockage of the human ether-a-go-go-related gene (hERG) encoded potassium ion (K+) channels. The hERG channel is one of the most important antitargets to be addressed in the early stage of drug discovery process, in order to avoid more costly failures in the development phase. Using a thallium flux assay, 4,323 molecules were screened for hERG channel inhibition in a quantitative high throughput screening (qHTS) format. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Previously reported MD studies showed that water is mainly present outside the membrane, with lower amounts present within the permeation pore to facilitate ion transportation through the pore [45]. Our findings are in line with previous reports that water is not abundantly present in the pore domain of open channel [44,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…Previously reported MD studies showed that water is mainly present outside the membrane, with lower amounts present within the permeation pore to facilitate ion transportation through the pore [45]. Our findings are in line with previous reports that water is not abundantly present in the pore domain of open channel [44,46,47].…”
Section: Discussionsupporting
confidence: 92%
“…Here, we have collected 15 works from the past five years that employ machine learning-based classification approaches to predict hERG inhibition [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. All of these works apply training datasets of more than 1,000 molecules (and up to tens of thousands in some cases [47,48]), and an overall majority presents two-class (active vs. inactive) classification (with the notable example of the 2015 study of Braga et al, who have introduced a third class of "weak blockers") [38].…”
Section: Herg-mediated Cardiotoxicitymentioning
confidence: 99%
“…Furthermore, we used Doddareddy's experimentally validated dataset (a total of 60 compounds: 50 agents from the Chembridge database and 10 from an in-house compound library) as an external validation set to assess the generalization ability of our models. In order to compare the performance of our models with others reported in the literature, we also used the same data sets as those in the literature, including Hou's (Wang et al, 2012;Wang et al, 2016), Zhang's (Zhang et al, 2016), Sun's (Sun et al, 2017), Siramshetty's (Siramshetty et al, 2018), and Cai's (Cai et al, 2019) data sets. Here, it is necessary to mention that an integrated data set of hERG blockade, which is the largest database to date, has been collected by Sato et al (2018).…”
Section: Data Setsmentioning
confidence: 99%